Fracture resistance of teeth obturated with Gutta percha and Resilon: An in vitro study - Baba, Suheel Manzoor (Medknow Publications, 2010)
AIM: The aim of this study was to evaluate and compare the fracture resistance of endodontically treated teeth filled with gutta percha and Resilon. MATERIALS AND METHODS: A total of 60 freshly extracted single rooted teeth are selected and their anatomical crown removed at the CEJ. All samples were instrumented with the Step-back technique. Samples were randomly divided into three groups of 20 samples each: Group A obturated by lateral condensation with gutta percha and AH plus sealer, Group B obturated by lateral condensation with Resilon; Group C recieved no filling. Restored teeth were subjected to compressive loading in a universal testing machine. The results of fracture resistance recorded and statistical analysis done. RESULTS: The mean and SD values for the groups are as follows: Group A-536.555 ± 128.816, Group B- 885.943 ± 194.410 and Group C- 591.066 ± 68.97. It was seen that samples of Group B showed the highest fracture resistance followed by Group C. Group A showed the least fracture resistance. CONCLUSION: The results of this study showed that filling the canals with Resilon increased the in vitro resistance to fracture of endodontically treated single canal teeth when compared with gutta percha.